1991
DOI: 10.26749/rstpp.124.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Phenetic affinities, variability and conservation status of a rare Tasmanian endemic Eucalyptus morrisbyi J.G.Brett

Abstract: Eucalyptus morrisbyi is a rare Tasmanian endemic confined to one larger population (c. 2000 mature individuals) and two smaller populations (c. 15 and 16 mature individuals) in southeastern Tasmania. Morphological studies within the informal superspecies "Gunnii" reveal Eucalyptus morrisbyi has closest affinities to low altitude populations of E. gunnii in southeastern Tasmania and yet has distinct, phenetic differences from that species. Levels of variation in E. morrisbyi populations appear comparable to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The evolutionary reasons for the clear genetically based differences in resistance of this endangered plant species are unknown, as are the reasons for differences in some of the traits that may confer this resistance. There is no evidence of seed or pollen flow between these two populations, and it is suggested that they have been genetically disjunct for thousands of years (Wiltshire et al 1991, Jones et al 2005), possibly contributing to the evolution of variation in herbivore resistance within this species. The genetic‐based resistance of the small RH population of E. morrisbyi may have evolved by chance alone through genetic drift and inbreeding causing alleles to accumulate over time (Wright 1931).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evolutionary reasons for the clear genetically based differences in resistance of this endangered plant species are unknown, as are the reasons for differences in some of the traits that may confer this resistance. There is no evidence of seed or pollen flow between these two populations, and it is suggested that they have been genetically disjunct for thousands of years (Wiltshire et al 1991, Jones et al 2005), possibly contributing to the evolution of variation in herbivore resistance within this species. The genetic‐based resistance of the small RH population of E. morrisbyi may have evolved by chance alone through genetic drift and inbreeding causing alleles to accumulate over time (Wright 1931).…”
Section: Discussionmentioning
confidence: 99%
“…Both populations occur in coastal dry sclerophyll woodland, at similar altitudes (25–80 m above sea level), have a west–southsouthwest aspect and a low mean annual rainfall (520–620 mm). These two populations are separated by approximately 20 km and are significantly genetically differentiated based on seedling morphology (Wiltshire et al 1991) nuclear microsatellite allele frequencies and chloroplast DNA markers (Jones et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cordata, E gunnii and possibly F. morrisbyi are the only plausible extant species. E. morrisb),i was not included in the progeny trial because of its extremely limited distribution (Wiltshire et aL 1990), and rhe fact rhat irs juveniles would be difficult to distinguish from E. gunnii in hybrid combination (e.g. Potts 1989).…”
Section: The Southern Group Comprised E Barberi Populations Frommentioning
confidence: 99%